Cytospora azadirachtae sp. nov.—A new species associated with dieback disease in Azadirachta indica from southern India - Joy, Josna; Mahesh, Madappa; Mahadevakumar, Shivannegowda; Maharachchikumbura, Sajeewa S. N.; Sridhar, Kandikere R; Chandranayaka, Siddaiah; Patro, Thanuku Samuel Sampath Kumar (Phytotaxa, 2024)
Stem cankers associated with dieback disease of neem (Azadirachta indica) shoots were collected from Manasagangotri and Doddamaragowdanahalli, Mysore, Karnataka (India) and based on microscopic, cultural and initial blast results of ITS-rDNA identified the isolated fungus to the genus Cytospora. The phylogenetic analysis based on nrITS-rDNA-tef1-α-tub2 sequence data showed it represents a new species and is described as Cytospora azadirachtae. The concatenated phylogeny revealed that Cytospora azadirachtae is phylogenetically distinct and closely related to Cytospora shoreae and C. rhizophorae. Cytospora rhizophorae differs from C. azadirachtae in that it has shorter conidia and conidiogenous cells. Further, C. rhizophorae is halotolerant and saprobic and shows host-specificity usually associated with Rhizophora sp. (R. mangle and R. mucronata). Similarly, C. shoreae differs from C. azadirachtae in having larger flask-shaped conidiomata and larger conidia. Based on multi-locus sequence and phylogenetic analysis of the canker and dieback disease symptoms, the present study introduces C. azadirachtae as a new species.